Anti Klimaks Implementasi E-Government: Analisis Partisipasi Masyarakat Petani Di Kabupaten Gunungkidul - Wicaksono, Ferri (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2018)
This research is located in Gunungkidul Regency, Yogyakarta Special Region (DIY). The rapid development of global information technology has driven a paradigm shift in society towards the era of digital society. This fact directs the massive use of electronic media in the public service bureaucracy in Indonesia. In order to realize a clean, transparent public service and be able to answer the demands of change effectively, in line with Presidential Instruction No. 3 of 2003. Dilemma when the Gunungkidul Regency Government is seeking e-government as a reform of the public service bureaucracy that is intended for the community as the recipient of service benefits, there are elements of farmer communities that tend to be difficult to adopt new technologies. The Gunungkidul Regency Government has consistently developed a website up to the sub-district level totaling 18 sub-districts and village levels totaling 144 villages with domains namely "name of village-sub-districts.desa.id", known as the Village Information System (SID). The author uses descriptive exploratory research methods to explain the limitations of peasant communities in the use of e-government. This situation can trigger barriers to optimizing the implementation of e-government in Indonesia. The author finds the limitations of the farming community in Gunungkidul Regency in the use of e-government due to 2 (two) aspects namely the lack of habituation in the use of information technology media and the characteristics of community associations that are inherent in the social activities of farmers in Gunungkidul Regency. The character of the farming community tends to be difficult to correlate with the development of digital information technology in its activities, making it difficult to create an habit of using internet media for everyday life.Â Keywords: e-government, public service, farmer community, limitations